Prevalence and host association of mosquito ectoparasites in cattle sheds of West Bengal, India - Susobhan Datta Mudi; Pranesh Paul; Susmita Roy; Debjit Mondal; Goutam K Saha; Gautam Aditya (International Journal of Tropical Insect Science, 2026)

Earlier transplanting increases Boro rice yield and water productivity by minimizing exposure to high temperature and salinity in the coastal Ganges Delta - Priya Lal Chandra Paul; Richard W. Bell; Edward G. Barrett-Lennard; Mohammed Mainuddin; Donald S. Gaydon; Mark Glover; Marta Monjardino; Debjit Roy; Md. Belal Hossain; Md. Nazrul Islam; Sukamal Sarkar (Field Crops Research, 2026)

Strategies of water resource utilization and agricultural water management in the coastal saline zone of Bangladesh - Md. Belal Hossain; Debjit Roy; Priya Lal Chandra Paul; Mst. Shetara Yesmin; Palash Kumar Kundu; Mohammad Rezoan Bin Hafiz Pranto; Md Aklimuzzaman; Mousumi Paul; Md. Maniruzzaman; Mohammed Mainuddin (Irrigation and Drainage, 2025)
Access to irrigation water is pivotal for dry season crops in the coastal saline regions of Bangladesh. This research investigates strategic measures aimed at ensuring water availability for polder agricultural purposes in the dry season. This study was performed from 2017 to 2022 to assess the water availability inside polders # 30 and # 31 in Khulna region of the south‐western coastal zone of Bangladesh. Our methodology encompassed diverse approaches: identifying optimal water sources, capturing low‐salinity water for agriculture, implementing crop–soil–water management to enhance cropping intensity, employing irrigation modelling for effective crop planning, utilizing GIS techniques to estimate water storage and conducting impact analysis using satellite images. Irrigation by trapped river water increased the yield of different crops by 13–56% compared with that of farmer‐managed plots. Polders # 30 and # 31 currently have approximately 136 and 190 km of good canals, which store 334 and 502 ha‐m of water, respectively, during the dry period. With the existing stored fresh water, a maximum of 6,680 ha and 10,040 ha of watermelon and a minimum of 334 and 502 ha of boro rice cultivation were possible in polders # 30 and # 31, respectively. However, the excavation of poor and dead canals could increase freshwater storage and crop coverage. The image analysis of polder #31 revealed an increase in crop coverage of 238% from 2017 to 2022, which might be attributed to the introduction of advanced water management technologies and salt‐tolerant cultivars as well as holistic extension approaches by different government organizations (GOs), non‐governmental organizations (NGOs) and farmers. This study will assist in formulating pathways for polder‐scale water management and cropping intensification in coastal saline zones.

Greenhouse gas emissions from dry season rice irrigation in Bangladesh - Md. Maniruzzaman; Jatish Chandra Biswas; Md. Belal Hossain; Mohammed Mainuddin; Debjit Roy; Mst. Shetara Yesmin; Palash Kumar Kundu; Md. Mozammel Haque (Mitigation and Adaptation Strategies for Global Change, 2025)
Pumping groundwater for irrigation in Bangladesh is a major energy-consuming process and mostly depends on diesel fuel, which is related to greenhouse gas (GHG) emissions. But that issue has not yet been addressed in Bangladesh. `In this study, we have estimated GHG emissions for dry season (DS) irrigated rice considering all irrigation devices with their lifting heads, area coverage, and water sources (surface and groundwater) and power sources (diesel and electricity) during 2019–2020. GHG emissions varied with locations, sources of irrigation, fuel and water sources used. Irrigation water driven GHG emission in Bangladesh is about 2.27 million tons (Mt) CO 2 e DS −1 , which is about only 4% of agricultural sector GHG emission. Groundwater pumps contributed the lion shares (2.04 Mt CO 2 e DS −1 ), and surface water pumps contributed only 0.23 Mt CO 2 e DS −1 . Based on the GHG emissions, Rajshahi Division is the main hotspot followed by Rangpur and Mymensingh Divisions, because of intensive groundwater used in these areas. Current deep tubewells (DTWs), shallow tubewells (STWs) and low lift pumps (LLPs) area coverage is about 19.2%, 56.8% and 24.0% of the total cultivable areas of the country; but it contributes about 49.1%, 40.6% and 10.3% of emitted GHG, respectively. The results revealed that withdrawal of groundwater is an important source of GHG emission. Therefore, expansion of surface water irrigation facilities with the adoption of different improved distribution systems, water and energy saving technologies like alternate wetting and drying practices, conservation agriculture along with water use-efficient varieties for rice cultivation can be promoted for reducing GHG emission.

Two-Photon Fluorescence Tracking of Colloidal Clusters - Debjit Roy; Dipankar Mondal; Debabrata Goswami (Journal of Fluorescence, 2016)